2020
DOI: 10.1142/s2424835520500034
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Distal Radius Fixations and Functional Outcomes in the Superelderly Population

Abstract: Background: Superelderly patients (defined as 80 years old and older) account for 18% of all distal radius fractures in our institution and this number is increasing with the ageing population. When faced with the option of surgery, patients in this age group have concerns with regards to the long term outcomes including functional outcomes and the time to fracture union. Therefore, the aim of this study was to evaluate the functional outcomes in this specific population. Methods: Patient selection for surger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 7 publications
0
7
1
Order By: Relevance
“…The complication rate varies widely in the literature. 16 , 17 , 18 , 19 , 20 Our complication rate appears high compared with the 3% rate described by Heng et al, 18 who observed patients aged over 80 years. However, their study did not include minor complications.…”
Section: Discussioncontrasting
confidence: 46%
See 1 more Smart Citation
“…The complication rate varies widely in the literature. 16 , 17 , 18 , 19 , 20 Our complication rate appears high compared with the 3% rate described by Heng et al, 18 who observed patients aged over 80 years. However, their study did not include minor complications.…”
Section: Discussioncontrasting
confidence: 46%
“… 2 This female predominance found in literature matches our results. 18 , 29 , 30 , 31 Moreover, distal radius fractures are often the result of a low-energy fall on an outstretched wrist. 3 , 32 Older independent patients in good cognitive health seem to be at higher risk of sustaining a distal radius fracture as they still have the reflex to put their arm forward when they fall.…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective study of 76 superelderly patients treated with a volar plate found that surgical fixation can yield a good functional outcome [ 40 ]. Other studies have found no significant relationship between malalignment after a DRF and functional outcome in older patients [ 8 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14] One study assessing this patient group after surgical fixation of distal radius fractures found that ORIF yields good functional outcomes and a low complication rate. 14 The purpose of our study was to evaluate the operative treatment of distal radius fractures in patients older than 80 years to determine functional outcomes and complication rates. We hypothesize that patients older than 80 years with distal radius fractures treated with ORIF will have good functional outcomes and low complication rates.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Most of the current data on surgical management of distal radius fractures in the elderly focus on patients older than 60 years; however, there is a lack of data on patients older than 80 years. [12][13][14] One study assessing this patient group after surgical fixation of distal radius fractures found that ORIF yields good functional outcomes and a low complication rate. 14 The purpose of our study was to evaluate the operative treatment of distal radius fractures in patients older than 80 years to determine functional outcomes and complication rates.…”
Section: Introductionmentioning
confidence: 99%